Communication change in ALS: engaging people living with ALS and their partners in future research. (3rd October 2019) - Judge, Simon; Bloch, Steven; McDermott, Christopher J.
Abstract: Objective: To involve people living with amyotrophic lateral sclerosis (plwALS) in the scoping and identification of research priorities related to the changes in ALS communication including the use of augmentative and alternative communication (AAC). Methods: Two focus groups of plwALS at early and late stages of change to speech intelligibility were carried out as a patient and participant involvement exercise. The transcriptions of these groups were analyzed thematically and compared between groups. Results: Aspects of anticipation, preparation, adaptation and partnership were identified as key to dealing with communication change as a result of ALS. In particular the involvement of partners was clearly significant, as was the impact on them as well as the plwALS. PlwALS successfully contributed to focus groups and the process of group discussion about communication itself appeared constructive. Conclusions: Research and new interventions should focus further on how to support the partners of plwALS. Future research with plwALS should place AAC strategies and technology in the context of wider communication and investigate how best to support the anticipation, preparation and adaptation to communication change. Specific areas of research need relating to this support are suggested. IMPLICATIONS FOR REHABILITATION: People living with ALS (plwALS) are rarely involved in setting the research agenda in the areas of speech and augmentative and alternative communication (AAC). Enabling plwALS to contribute to research, even those with no speech, is feasible with appropriate support. Feedback indicates that communication change and AAC are experienced in different ways by plwALS. Research and intervention should focus on how to support the anticipation, preparation and adaptation to communication change for plwALS.